Antimicrobial resistance in Gram-negative bacteria from retail meat: Prevalence and public health implications - Safia Arbab; Hanif Ullah; Weiwei Wang; Anwar Shahzad; Abdullah A. Aseeri; Fuad M. Alzahrani; Khalid J. Alzahrani; Khalaf F. Alsharif; Jiyu Zhang (PLoS ONE, 2026)
Retail meat is an important source of nutrition, but it may also serve as a reservoir of antimicrobial-resistant Gram-negative bacteria, posing a significant public health concern. This study investigated 123 retail meat samples collected from outlets in Sindh, Pakistan, including locally produced raw ground meat, imported raw ground meat, raw beef burgers, frozen chicken portions, and swabs from the outer surfaces of chicken carcasses, to identify Gram-negative bacteria and assess their antimicrobial susceptibility patterns. Gram-negative bacteria were recovered from all samples. Among the isolates, Escherichia coli was the most prevalent (37.4%), followed by Klebsiella spp. (25.2%), Salmonella spp. (17.9%), Enterobacter spp. (13.8%), Pseudomonas spp. (2.4%), Citrobacter spp. (2.4%), and Aeromonas spp. (0.8%). Identification was based on culture characteristics, Gram staining, biochemical testing, and API 20E confirmation. Antimicrobial susceptibility testing showed high levels of resistance among the isolates, particularly to ampicillin, amoxicillin-clavulanate, cefotaxime, ceftazidime, and ceftriaxone. E. coli , Klebsiella spp., Salmonella spp., and Enterobacter spp. exhibited substantial multidrug resistance, while comparatively lower resistance was observed for cefepime, gentamicin, and piperacillin-tazobactam in some species. Overall, resistance to multiple antimicrobial classes was common, indicating the widespread presence of multidrug-resistant Gram-negative bacteria in retail meat. These findings highlight the potential role of retail meat as a source of antimicrobial-resistant bacteria in the food chain and underscore the need for strengthened surveillance, improved hygiene practices, and antimicrobial stewardship in food animal production. A One Health approach is essential to help limit the spread of antimicrobial resistance across human, animal, and environmental sectors.